2020
DOI: 10.4097/kja.19111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding dexmedetomidine to local infiltration of bupivacaine on postoperative pain in pediatric herniorrhaphy: a randomized clinical trial

Abstract: Indirect inguinal hernia, caused by a patent processus vaginalis, is a common pathology in the first year of life, especially in low-birth weight male neonates [1]. Surgery (inguinal herniorrhaphy) is considered to be the first-line treatment, in which various techniques, such as open and laparoscopic procedures, have been proposed [2]. Nevertheless, despite the variety of techniques proposed for correction of inguinal hernia, herniorrhaphy is associated with severe adverse effects, such as recurrence, and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…No serious adverse effects were recorded throughout our study. These findings are equivalent to most of the studies using these drugs as an adjuvant to LA in various types of blocks (Azemati et al., 2019; Mostafa, Aal, et al., 2020; Ragaa et al., 2019). Dexmedetomidine was found to significantly increase sedation and analgesia and decrease blood pressure and HR in a concentration‐dependent manner because of its potent analgesic, sedative and sympatholytic properties (Ho et al., 2005; Kanazi et al., 2006; Mostafa, Herdan, et al., 2020).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…No serious adverse effects were recorded throughout our study. These findings are equivalent to most of the studies using these drugs as an adjuvant to LA in various types of blocks (Azemati et al., 2019; Mostafa, Aal, et al., 2020; Ragaa et al., 2019). Dexmedetomidine was found to significantly increase sedation and analgesia and decrease blood pressure and HR in a concentration‐dependent manner because of its potent analgesic, sedative and sympatholytic properties (Ho et al., 2005; Kanazi et al., 2006; Mostafa, Herdan, et al., 2020).…”
Section: Discussionsupporting
confidence: 84%
“…The findings of higher parents’ satisfaction scores in this study that were significant in the dexmedetomidine‐treated group compared to the LA‐only group add to the superior analgesia and sedation profile of this drug when used as an adjuvant to LA in the paediatric population (Azemati et al., 2019). The current study showed that the average SpO 2 , MAP, HR and EtCO 2 levels recorded over time for all patients in the three study groups were stable and within the acceptable limits in these settings, with no noticeable statistically significant difference among the groups.…”
Section: Discussionmentioning
confidence: 65%
“…315 potentially relevant articles are identi ed initially. Finally, six RCTs are included in the meta-analysis [11,13,[17][18][19]25].…”
Section: Resultsmentioning
confidence: 99%
“…The dose of dexmedetomidine ranged from 0.3 µg/kg to 1.0 µg/kg. Among the six included RCTs, two trials reported analgesic consumption [19,25], two trials reported number of rescue analgesics and time to rst analgesia [18,19], two trials reported emergence agitation [18,25], as well as two trials reported pain scores at 1 h and 2 h [17,19]. Jadad scores of the six included studies vary from 3 to 5, and all six studies have high-quality based on the quality assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation